Design and Implementation of a LabVIEW-Based Real-Time Temperature Monitoring and Communication System Using MAX6675 Thermocouple - Isminarti Isminarti; Muhammad Fais Dwi Saputra; Dhidit Ferdiansyah; Nurhikmah Fajar; Fauziah Fauziah (Jurnal Ilmu Komputer (JUIK), 2026)
This research aims to design and implement a temperature monitoring system that utilizes the Thermochouple Max6675 sensor, Arduino Nano, as well as communication modules, namely RS485 to TTL and RS485 to USB. This system is equipped with a Solid State Relay to control the device based on the detected temperature measurements. The Max6675 sensor is used to measure temperature accurately and then sends the data via RS485 communication to the user's device. To ensure the accuracy of the measurement results, the temperature obtained from this system is compared with temperature data obtained from the Hygrothermometer application as a standard reference for the surrounding environmental temperature. In this circuit, the data measured by the sensor is sent via RS485 to TTL and forwarded using RS485 to USB to the computer user. The received temperature data is then processed and displayed in real time via the Labview application, providing a bright graphical interface for users to integrate temperature changes. In the tests carried out, the results obtained from the Max6675 sensor compared with the Hygrothermometer application showed a fairly high level of accuracy, namely around 90%. Which shows that the system developed is able to provide temperature measurements with a low error rate. Using the Labview application as a platform for displaying monitoring results makes it easy to visualize temperature data directly and allows further processing for real-time temperature analysis. This system has great potential to be applied in various industrial fields, such as temperature monitoring in manufacturing processes or environmental control, with a sufficient level of accuracy and easy integration with other software for analysis and control purposes. The success of this research opens up opportunities for more efficient, cost-effective temperature monitoring and also a higher level of accuracy.